2016
DOI: 10.1111/modl.12328
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Zipfian Frequency: L2 Acquisition of English Prenominal Past Participles

Abstract: This study examined the effectiveness of Zipfian frequency at facilitating the acquisition of English prenominal past participles. Chinese middle school students (N = 103) were randomly assigned to a sequenced Zipfian frequency (SZF) group, a random Zipfian frequency (RZF) group, a balanced frequency (BF) group, and a control group. A mixed experimental design was used to detect the development of the learners' prenominal past participles. An untimed acceptability judgment task and a timed grammaticality judgm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
(130 reference statements)
0
13
0
Order By: Relevance
“…Dong and Zhang (2017) probed how Zipfian and balanced input affected L2 development of English pronominal adjective participles and object-extracted relative clauses. They observed that Zipfian input was superior to balanced input in L2 learning of English pronominal adjective participles, confirming the conclusion of Zhang and Dong (2016), while the two distributions played no differential role in L2 development of object-extracted relative clauses. They concluded that the two distributions may not differ in the L2 learners’ development of abstract constructions.…”
Section: Frequency Distribution In Language Learning: Zipfian Vs mentioning
confidence: 67%
See 2 more Smart Citations
“…Dong and Zhang (2017) probed how Zipfian and balanced input affected L2 development of English pronominal adjective participles and object-extracted relative clauses. They observed that Zipfian input was superior to balanced input in L2 learning of English pronominal adjective participles, confirming the conclusion of Zhang and Dong (2016), while the two distributions played no differential role in L2 development of object-extracted relative clauses. They concluded that the two distributions may not differ in the L2 learners’ development of abstract constructions.…”
Section: Frequency Distribution In Language Learning: Zipfian Vs mentioning
confidence: 67%
“…The token frequency of each verb in the balanced input of Year and Gordon (2009) was eight, almost four times as high as that in Goldberg et al (2004), Zhang and Dong (2016), and Dong and Zhang (2017). Also, the token frequency of exemplars in the Zipfian input varied, with eight times in Goldberg et al (2004) and McDonough and Nekrasova-Becker (2014), twenty-four times in Year and Gordon (2009), seven times in Zhang and Dong (2016), twelve times in McDonough and Trofimovich (2013), and fifteen times in Fulga and McDonough (2016). Great variance in token frequencies in the intended input is likely to influence the observed effects of input distributions, since Zhang and Ma (2014) found that six occurrence events are enough for L2 learners to acquire a new instance of a VAC.…”
Section: Frequency Distribution In Language Learning: Zipfian Vs mentioning
confidence: 78%
See 1 more Smart Citation
“…As shown by previous research into the facilitative effects of Zipfian frequencies (e.g. Zhang and Dong 2016), the exposure of learners to prototypical construction (such as PV-ASC attachment patterns) is advantageous. What underlies this task is presumably the most fundamental of all assumptions in ACCxG, namely that, at early stages of language acquisition, the inclusion of specific PVs should be guided by natural occurring categories (Rosch et al 1976), rather than abstract, arbitrarily assigned levels of linguistic difficulty.…”
Section: )mentioning
confidence: 93%
“…Many studies have found no major advantage for either skewed or balanced input in the acquisition of a new construction by FL learners. These studies cover a range of constructions and participants, such as prenominal adjective participles (Zhang & Dong, 2016) and relative clauses (Zhang & Dong, 2019) in teenaged Chinese learners of English, Russian morphology in U.S. college students (Brooks, Kwoka, & Kempe, 2017), and past counterfactuals (Révész, Sachs, & Hama, 2014) and Esperanto transitives (Fulga & McDonough, 2016) in ESL students. The tasks employed to examine the effect of input also vary, including grammaticality judgement (Zhang & Dong, 2016), written production (Zhang & Dong, 2019), forced‐choice comprehension (Fulga & McDonough, 2016; Révész et al., 2014), and oral production (Brooks et al., 2017; Révész et al., 2014).…”
Section: Literature Reviewmentioning
confidence: 99%